1999
DOI: 10.1046/j.1523-1755.1999.00389.x
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of excess weight on mortality and hospital stay in 1346 hemodialysis patients

Abstract: Adequate dialysis with special attention to proper nutrition aimed to achieve the high end of normal BMI may help to reduce the high mortality and morbidity in hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
246
3
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(277 citation statements)
references
References 8 publications
17
246
3
6
Order By: Relevance
“…34,35 In contrast to trends seen in the general population, higher BMI has generally not been associated with an increase in mortality rate in patients receiving HD. [36][37][38][39][40][41] Johansen et al 40 reported that body fat and muscle mass, surrogates of body size, were both associated with improved survival in obese patients receiving HD, whereas Beddhu et al 42 showed that urinary creatinine level as a surrogate of muscle mass has a stronger association with survival than does body fat. 39,43 Only a very few studies have failed to confirm the survival advantages of obesity in patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 In contrast to trends seen in the general population, higher BMI has generally not been associated with an increase in mortality rate in patients receiving HD. [36][37][38][39][40][41] Johansen et al 40 reported that body fat and muscle mass, surrogates of body size, were both associated with improved survival in obese patients receiving HD, whereas Beddhu et al 42 showed that urinary creatinine level as a surrogate of muscle mass has a stronger association with survival than does body fat. 39,43 Only a very few studies have failed to confirm the survival advantages of obesity in patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing BMI among patients who initiate dialysis certainly will influence the total number of patients who receive dialysis in the next decade. In contrast to the general population (13), obesity is associated with improved survival (10,14,15) and decreased hospitalization rates (10) among patients with ESRD. Using data on Ͼ400,000 incident dialysis patients during the period 1995 to 2000, Johansen et al (10) noted an approximately 20% lower mortality risk among those with a BMI Ͼ37 kg/m 2 at dialysis initiation compared with patients with a BMI between 22 and Ͻ24.9 kg/m 2 at dialysis initiation.…”
Section: Discussionmentioning
confidence: 99%
“…[3,4] Similarly, extremes of underweight have recently been described as a risk factor for surgery. [5][6][7] Several recent studies of critically and chronically ill patients, [8][9][10][11] and of patients undergoing certain procedures [12][13][14][15] suggest that overweight and obese patients may paradoxically have better outcomes than underweight patients, given an increased risk for death and catastrophic complications in the latter patients.…”
Section: Introductionmentioning
confidence: 99%